Marketing Mix to Increase Sales of Wedding Package Resort Buyout at Alila Villas Uluwatu - Ida Ayu Dwi Gangga Laraswati; I Ketut Sutama; I Ketut Suarja; Made Sudiarta; I Ketut Suja (The Postgraduate School of Tourism Sahid Polytechnic, 2024)
Purpose: The purpose of this research is to determine strengths, weaknesses, opportunities and threats of an effort to increase sales of wedding package resort buyout, to find out marketing mix strategy that should be used by Sales & Marketing Department to increase sales of wedding package resort buyout. Research methods: Data collection methods that used were participation observation, interview, documentation, and questionnaire. The analysis technique that used are qualitative descriptive analysis, quantitative descriptive analysis, Internal Factor Analysis Summary (IFAS) matrix, External Factor Analysis Summary (EFAS) matrix, Internal-External (IE) matrix, and SWOT analysis. Results and discussion: The result of the research show that there are internal and external factors that influence the increase in upselling which carried out by Sales & Marketing Department at Alila Villas Uluwatu. Based on SWOT analysis score of IFAS was 2.88 and score EFAS was 2.86 that made the position of Alila Villas Uluwatu in current condition in cell 5, named the strategy of concentration through horizontal integration or stability (no change in profit). It means that this company is in a moderate attractive industry, the strategy that used has the goal relatively more defensive, namely to avoid losing sales and losing profits. Based on the SWOT analysis, alternative strategies that can be used to increase the sales of wedding package resort buyout is obtained by finding new markets, adding wedding inclusion on the wedding package, improving the payment regulation, making new building for attendees and equipment store, and making competitor list that shows if hotel is competed to the competitors. Implication: The advice given to the management of Alila Villas Uluwatu is to add new markets that are potential guests who hold wedding resort buyout such as India and Singapore, add more inclusions to the wedding package in order to make the guests interested, and improve the payment regulations to make the wedding operational runs better. Keywords: Marketing mix, IFAS matrix, EFAS matrix.